THE SYNTHESIS OF GLYCEROL CARBONATE FROM BIODIESEL BYPRODUCT GLYCEROL AND UREA OVER AMBERLYST 36 - Senania, Astri; Sulistyo, Hary; Prasetya, Agus (Jurnal Bahan Alam Terbarukan, 2017)
The increasing use of biodiesel as renewable fuels leads to the increasing of glycerol amount as a byproduct of biodiesel production. One of the glycerol derivative products that is environmentally friendly and renewable is glycerol carbonate. Glycerol carbonate is commonly used as a raw material for polymers, surfactants, emulsifiers, lubricants, paints, also used in the cosmetics and pharmaceutical industries. In this study, the research was carried out by using a batch reactor with a three-neck flask equipped with reverse cooling, thermometers, mercury stirrer, and heating mantle with the conditions of the reaction temperature around 373 â€“ 413 K, mole ratio of reactants of urea: glycerol were 1:0,5, 1:1, 1:1,5, 1:2 and 1:4Â  and the concentration of catalyst were 1%, 2%, 3%, 4% and 5% respectively. Reaction was done for four hours. The results showed that the formation of glycerol carbonate from glycerol and urea using a catalyst Amberlyst 36 is affected by the catalyst concentration, reaction temperature and the ratio of reactants used. The highest glycerol conversion was obtained at 55.07% at a temperature of 393 K with mole ratio of urea and glycerol 1:0,5 and the percentage of catalyst 3% of the amount of glycerol.